Developing English Learning Media Using Edpuzzle for Understanding Language Expressions in a Listening and Speaking Class - Supriusman, Supriusman; Daud, Afrianto; Mahdum, Mahdum; Hadriana, Hadriana; Kurniawan, Andri (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research aimed to develop an English learning medium using Edpuzzle to understand language expressions in listening and speaking classes. A Research and Development (R&D) design was employed in this study, using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) as the development model. Data were collected through an online questionnaire consisting of a set of written statements for respondents to answer. Descriptive analysis was utilized as the technique for data analysis, dealing with quantitative data. Four Edpuzzle-based videos, featuring explanations and quizzes, were developed and validated by media and language experts. The validation results revealed that the video 'Invitation' achieved an average score of 4.25 (valid), the video 'Apologizing, Expressing Anger and Resolving Conflict' scored an average of 4.30 (valid), the video 'Giving Compliments and Replying to Compliments' received an average score of 3.81 (quite valid), and the 'Expressing Opinions' video garnered an average score of 3.91 (quite valid). Overall, the average score was 4.10, categorized as valid. Therefore, the Edpuzzle-based video, as a developed English learning medium, was deemed suitable and appropriate for application in listening and speaking classes in Indonesia.